Oral health attitude and behavior among health-care students in a teaching hospital, Telangana State: A cross-sectional study - Ravi Kiran Jella; K. V. N. R. Pratap; T Madhavi Padma; V Siva Kalyan; P Vineela; L Surya Chandra Varma (Wolters Kluwer Medknow Publications, 2016)
Introduction: The behavior of health-care students and their attitudes toward their own oral health reflect not only understanding of the importance of preventive dental procedures but also in improving the oral health of their patients. Thus, the aim of the study is to enlighten self-reported attitude and behavior among dental and medical undergraduate students. Methodology: A cross-sectional, questionnaire-based study was conducted among undergraduate students of a tertiary care teaching hospital in Telangana state. The information regarding demographic data, attitude, and behavior toward oral health was collected using the Hiroshima University-Dental Behavioral Inventory questionnaire. Data were analyzed using the analysis of variance. Results: The study subjects consisted of 361 dental and 315 medical undergraduate students. The present study revealed that oral health attitudes and behavior improved significantly with increasing levels of education in both dental and medical students. The dental undergraduates have better attitude and behavior than medical students, which was statistically significant regarding oral hygiene practices, gingival health, and visit to the dentist. Conclusions: Significant improvement was found regarding oral health attitude and behavior among both dental and medical students, with increase in their academic year. The overall attitude and behavior were better in dental students than medical students; however, both dental and medical undergraduates should have a comprehensive program, self-care regimen practices starting from their 1st year of education.